HUBUNGAN KECANDUAN GAME ONLINE DENGAN PERILAKU AGRESIF MAHASISWA DIMASA PERKULIAHAN DARING - Fitri Amelia; Safri Safri; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Based on Asosiasi Penyelenggaraan Jasa Internet Indonesia (APJII) survey in 2018, the number of internet users in Indonesia, 88.5% are in the 20-24 years age range and 92.1% are students. The most popular use of the internet for students is entertainment in particular online games. The purpose of this study was to determine the relationship between online game addiction and student aggressive behavior during online class. This study used a cross-sectional approach with a total sample of 341 studens who were selected using a proportional stratified random sampling technique. Data were collected using a questionnaire and were. Analysed using a chi-square test. The results of this study showed that there was a significant relationship between online game addiction and aggressive behavior with a pvalue of 0.00 <0.05. Further analysis showed that the odds ratio is 5.311, meaning that each respondent who has an addiction tends to behave aggressively 5.311 times than those who are not addicted to games. The contingency coefficient value is 0.287 where the strength of the relationship is sufficient and positive, so the two variables have a unidirectional relationship. Based on these results,it suggests that students have to pay attention to the intensity of playing time and maintain their emotions when playing online games so it can avoid them for doing overdo and become addicted and aggressive. Keywords: addiction, aggressive behavior, online class , online game , student